The influence of functional movement screen results on the frequency of sports injuries in soccer players - Kryger, K.; Wieczorek, A.; Wieczorek, J.; Sliwowski, R. (Central European Journal of Sport Sciences and Medicine, 2019)
Functional Movement Screen (FMS) is a functional screen test of the motor system which is steadily gaining recognition and popularity among individuals interested in prevention of sports injuries. The FMS test battery includes seven mutually related motor activities to analyse the quality of basic movement patterns. An in-depth interpretation of the performed test design provides good conditions to determine the weakest links in the kinematic chain and to estimate the risk of injury. The objective of this study was to determine the effect of the FMS test results on frequency of sports injuries in soccer players. With the main objective of the study in mind the following research hypothesis was formulated: "a group of players in the lowest interval (14-17 FMS test points) will have a high frequency of injuries in comparison to a group in the upper interval (18-21 points in the FMS test)". The tests were carried out on a group of 102 younger and older junior soccer players representing the Soccer Academy of KKS Lech Poznan. For that the test design with FMS test procedure was used, followed by a six month period in which the injuries of the individuals in the study group were recorded. The research hypothesis was not confirmed. In the analysis of the results no statistical significance was noted between the total number of points obtained in the FMS test and the number of injuries. It was noted that the number of injuries was statistically significantly correlated with the results of the Shoulder Mobility test of the right side (for all participants and for the players in the lower interval), Hurdle Step test of the left side (for a group of players in the lower interval), and the In-line Lunge test of the left side (for upper interval players). The results of the single variable logistic regression showed that injuries occurred more often in players of the lower interval. A forest plot indicates the direction of the increased risk of injury in players in the lower interval of points: OR = 1.14 (95% CL; 0.71 : 1.83).